Longitudinal match running performance analysis of soccer in professional European leagues: A systematic review - Ponce-Bordon, J. C.; Lopez-Gajardo, M. A.; Lobo-Trivino, D.; Pulido, J. J.; Garcia-Calvo, T. (International Journal of Performance Analysis in Sport, 2024)
This systematic review aimed to poll the current literature on match running performance in soccer matches in the European leagues with a longitudinal perspective. An electronic database search (Web of Science, Scopus, SportDiscus, and PubMed) was conducted (until 30 January 2024). Potential studies were searched by using different combinations of groups of keywords and criteria: including being about professional soccer in European leagues, measuring match running performance, and using tracking technology to measure players` performance. A total of 3,756 papers were reviewed and after two screening phases, a total of 41 papers were selected. This review showed that total distance (TD) covered by soccer players in full matches ranged from 11,393 ± 1,016 m in the earliest season to 10,698 ± 844 m in the most recent season. Also, a decrease in the second halves of matches was found in TD. A wide range of speed thresholds was found to record the high-speed running (HSR) and a light trend towards an increase was reported by HSR. In addition, match analysis outcomes per playing positions reported a wide variety of physical profiles. The authors suggest the need to understand the evolution of match running performance to optimise soccer players performance.